Use of the 0.027-inch VIA microcatheter for delivery of Pipeline Flex: a technical note. (1st February 2017) - Lin, Li-Mei; Colby, Geoffrey P; Bender, Matthew T; Xu, Risheng; Huang, Judy; Tamargo, Rafael J; Coon, Alexander L
Abstract : Background: The Pipeline Embolization Device (PED; Medtronic Neurovascular, Irvine, California, USA) is designed for delivery through a 0.027″ microcatheter. Challenges with the second-generation PED Flex include limited support from the Marksman microcatheter for consistent resheathing and transmission of push forces for device delivery. The VIA27 (Sequent Medical/MicroVention Terumo, Tustin, California, USA) is an alternative 0.027″ microcatheter originally designed for intrasaccular flow diverter delivery. Here we describe our experience with the VIA27 in the delivery of PED Flex. Methods: We retrospectively identified patients who underwent PED Flex treatment with the VIA27 microcatheter at our institution. Patient demographics, aneurysm characteristics, equipment utilized, and procedural details were documented. Results: A total of 127 cases were completed using the VIA27 microcatheter for PED Flex implantation. Mean patient age was 56.8±12.4 years (range 21–86 years). All but one of the cases were treatments for intracranial aneurysms. Average aneurysm size was 6.5±6 mm (range 2–38 mm). Of the 127 cases, 120 (95%) were anterior circulation cases and 7 (6%) were posterior circulation cases. Significant cervical internal carotid artery (ICA) tortuosity was present in 33/120 cases (28%). Moderate to severe cavernous ICA tortuosity was present in 54/120 cases (45%). Mean fluoroscopy time was 34.1±22.7 min. Large diameter PED devices (4.5–5 mm) were used in 42/127 cases (33%). Balloon post-processing of the PED was used in 15/127 cases (12%) to improve vessel wall apposition of the PED. Conclusions: The VIA27 is a microcatheter capable of successful PED Flex delivery in neurointervention. We have shown its utility in enhancing both resheathing and push for optimal PED Flex implantation. The VIA27 microcatheter may be a useful and safe adjunct to the traditional Marksman microcatheter in PED Flex treatment of the cerebrovasculature.